Appraisal and repair of timber structures. - Lawrence, Andrew, MA (Cantab); Ross, Peter (Consultant) (ICE Publishing, 2020)
Addressing the potential problems that can occur in all types of timber construction, from fungal and insect attack, through to structural inadequacy to accidental damage, this guide tells how to identify, remedy and repair the problems in detail.